Solve for "x" in 2x^2 - x - 1 = - 1
First: set the equation to "0" > add "1" to both sides...
2x^2 - x - 1 + 1 = - 1 + 1
2x^2 - x + 0 = 0
2x^2 - x = 0
Sec: factor the expression > find the greatest common factor...
x(2x - 1) = 0
Third: you have two x-variables to solve for > set both x-variables to "0"...
a. x = 0
b. 2x - 1 = 0
2x - 1 + 1 = 0 + 1
2x = 1
2x/2 = 1/2
x = 1/2
solutions: 0 and 1/2
2007-01-25 16:38:28
·
answer #1
·
answered by ♪♥Annie♥♪ 6
·
1⤊
0⤋
First add 1 to each side:
2x^2 - x = 0
Now factor x out
x(2x-1) = 0
so x = 0 or 2x - 1 = 0, which means x = 1/2
You have two solutions: x = 0 or 1/2
2007-01-25 16:39:01
·
answer #2
·
answered by Ken M 3
·
1⤊
0⤋
to exhibit powers, the convention without an prolonged personality set is to apply the '^' image, so a ability might want to coach as 2x^2 -x =a million. yet on to the challenge. that is component-able. 2x^2 -x =a million 2x^2 -x -a million =0 (2x+a million)*(x-a million)=0 first answer - 2x+a million=0 2x= -a million x = -a million/2 second answer - x-a million=0 x=a million
2016-12-03 01:44:04
·
answer #3
·
answered by lesure 4
·
0⤊
0⤋
2x^2-x-1=-1
Add -1 from both sides:
2x^2-x=0
Factor out an x:
x(2x-1)=0
x=0
2x-1=0
x=0 and 1/2
Check:
2(1/2)^2-1/2-1=-1
2(1/4)-1/2-1=-1
1/2-1/2-1=-1
-1=-1
2(0)^2-0-1=-1
-1=-1
I hope this helps!
2007-01-25 16:43:05
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
2X2-X-1=-1
4X-X-1+1=0
3X=0
X=0/3
X=0
2007-01-25 17:34:07
·
answer #5
·
answered by Sarbjit 1
·
0⤊
0⤋
2x^2-x-1=-1
So,
2x^2-x=0
x(2x-1)=0
x=0 or x=0.5
2007-01-25 16:38:40
·
answer #6
·
answered by Keeper of Barad'dur 2
·
1⤊
0⤋
2X(2)-X-1=-1
2x(1)-x=-1
2x-x=-1
x=-1
2007-01-25 16:42:07
·
answer #7
·
answered by XFNET 2
·
0⤊
2⤋